(untitled) (Global Journal of Medical Research, 2024)
Introduction: Understanding that cancer is a pathology that is challenging to detect, treat, and comprehend is what makes the study of cancer so important. The goal of this case study is to show how a 20-year-old woman was affected by a variety of factors and symptoms that, when combined, raised suspicion of Ewing’s sarcoma, the second most common primary tumor in children and young adults. Ewing’s sarcoma has the characteristics of being an aggressive malignancy originating in the bones.